Fostering L2 Motivation in ESL: A Comprehensive Literature Review (2017-2021) - Singh, Amrendra Kumar (Development in Language Studies, 2023)
Corrective Over the past few years, ESL research on motivation has examined its complexity and multi-dimensionality. From 2017 to 2021, studies examined individual variations, social context, instructional approaches, and learner views as motivators for ESL learners. Research has shown that fostering learner autonomy and self-regulated learning practices motivates ESL students. Social considerations encourage ESL learners in other studies. From 2017 to 2021, ESL motivation research has stressed the need to evaluate numerous individual and environmental elements that affect language learning motivation. Promoting learner autonomy, self-regulated learning practices, positive teacher-student contact, and low language anxiety may motivate ESL learners and improve learning outcomes. Research on motivation in English as a Second Language (ESL) has identified various factors that can influence learners' motivation. These factors can be categorized into individual, social, and contextual factors.